Comparison of the Active Sitting Test and Head-Up Tilt Test for Diagnosis of Postural Tachycardia Syndrome in Children and Adolescents - Cai, Hong; Wang, Shuo; Zou, Runmei; Liu, Ping; Li, Fang; Wang, Yuwen; Wang, Cheng (Frontiers in Pediatrics, 2021)
Objectives: We aimed to compare the hemodynamic responses to the active sitting test with the passive head-up tilt test (HUTT) in children and adolescents with postural tachycardia syndrome (POTS). We hypothesized that sitting tachycardia was also present in POTS patients during sitting. Materials and methods: We tested 30 POTS patients and 31 control subjects (mean age = 12 years, range = 9–16 years) who underwent both active sitting test and HUTT successively. We measured the heart rate (HR) and blood pressure (BP) during each test. Results: For both POTS patients and control subjects, the HUTT produced significantly larger HR and BP increases from 3 to 10 min of postural change than did the sitting test. Moreover, POTS patients with excessive orthostatic tachycardia during the HUTT also had significantly larger increases in HR at all test intervals during the sitting test than did the control subjects. A maximum increase in HR ≥ 22 bpm within 10 min of the sitting test was likely suggested to predict orthostatic tachycardia, yielding a sensitivity and specificity of 83.3 and 83.9%, respectively. Only six of 30 POTS patients (20%) reached the 40-bpm criterion during the sitting test, and no one complained of sitting intolerance symptoms. Conclusions: We have shown that POTS patients also have sitting tachycardia when changing from a supine position to a sitting position. We believe that the active sitting test is a reasonable alternative maneuver in assessing POTS in population groups that cannot tolerate the standing test or HUTT.